The First Peasant and His Fellow Travelers: State Control over Greek Agricultural Institutions under Metaxas. - Panagiotopoulos, Dimitris; Carmona-Zabala, Juan (Cambridge University Press, 2019)
State control over Greece’s agricultural institutions increased during Metaxas’ authoritarian regime (1936-1941). Analyzing such state control allows us to address, in the Greek context, two questions with regard to fascist agrarian regimes. First, considering the trajectory of agricultural policy before the emergence of these regimes, how much of what they did was new, and how much was not? Second, how did the cadres of agricultural specialists participate in, or at least accommodate, the new regimes? Our research shows that Metaxas received support from the agronomists that had been active in Greece under previous liberal administrations. Such support did not take the form of laudatory statements or ideologydriven activism. It was rather a discreet acceptance of the new circumstances, combined with defection from one’s previous political camp. Metaxas’ dictatorship inherited most traits that made it a fascist agricultural regime from previous liberal administrations.
Política de acceso abierto tomada de: https://www.cambridge.org/core/services/open-access-policies/open-access-journals/green-open-access-policy-for-journals
Keywords: Grecia - Política y gobierno - S. XX; Agricultura - Grecia - S. XX; Greece; Agricultural fascism; Authoritarianism; Agricultural institutions; Rural history; Interwar period